Sistem Kendali dan Pemantauan Inkubator pada Telur Bebek Berbasis Internet of Things (IoT) - Handayani, Nia; Rismawan, Tedy; Nirmala, Irma (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The process of hatching duck eggs still uses manual methods, namely by incubating the brood directly or incubating other birds. Over time, farmers began to use hatching machines (incubators) to hatch duck eggs. The use of incubators still controls and monitors manually, namely checking the temperature and humidity of the incubator is still done by the breeder periodically and reversing the position of the eggs is still done one by one by hand. This research aims to build a system that can control and monitor duck egg hatching using incubators automatically and manually based on the Internet of Things using DHT22 sensors, ultrasonic sensors and PIR sensors. The effect of the implementation of the incubator control and monitoring system on duck egg hatching, which can maintain the egg hatching environment in the incubator based on ideal parameters without having to be monitored directly by the breeder. The system can be controlled automatically and manually through the website and successfully hatch 10 fertile eggs within 29 to 30 days. The condition of the hatched ducklings is also healthy, no defects. DHT22 sensor readings in testing the entire system get good results with an average error value of 0.87% for temperature and 3.91% for humidity. The DHT22 sensor reading value ensures that the temperature and humidity in the incubator are maintained by controlling the on and off of two lights and two fans. Furthermore, the ultrasonic sensor readings in the overall system test also obtained good results with an average sensor error value of 0.19%. The distance of water in the container can be maintained because the system can control the on and off of the water pump. Then, the PIR sensor readings in the overall test successfully detected all movements of the duck eggs that hatched in the incubator so that the system can provide warnings in the form of buzzer sounds and pop-up notifications on the website.